2017
DOI: 10.1111/gbb.12431
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus mapping and analysis of heritable variation in affiliative social behavior and co‐occurring traits

Abstract: Humans exhibit broad heterogeneity in affiliative social behavior. Twin and family studies show that individual differences in core dimensions of social behavior are heritable, yet there are knowledge gaps in understanding the underlying genetic and neurobiological mechanisms. Animal genetic reference panels (GRPs) provide a tractable strategy for examining the behavioral and genetic architecture of complex traits. Here, using males from 50 mouse strains from the BXD GRP, 4 domains of affiliative social behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 151 publications
(297 reference statements)
4
26
0
Order By: Relevance
“…The three-chamber social approach assay has come under recent criticism due to how dependent it is on activity levels of mice and its lower heritability compared to tests of direct social interaction (53). The CD animals had not previously been tested in this procedure excatly, but have been tested in a modified social approach where the time spent investigating a mouse in a cup is measured but with no competing non-social stimulus (28, 46, 47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-chamber social approach assay has come under recent criticism due to how dependent it is on activity levels of mice and its lower heritability compared to tests of direct social interaction (53). The CD animals had not previously been tested in this procedure excatly, but have been tested in a modified social approach where the time spent investigating a mouse in a cup is measured but with no competing non-social stimulus (28, 46, 47).…”
Section: Discussionmentioning
confidence: 99%
“…Direct social tasks have higher heritability than the three-chamber social approach and offer a more natural social experience (53), which may make them a more sensitive assay for testing social behaviors. Direct tasks have shown that Gtf2i models have increased nose-to-nose investigation time (36), mouse models lacking the proximal end of the region have increased investigation frequency (29), and Gtf2ird1 mutants make fewer aggressive actions but show increased following time (30).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study is the first to demonstrate individual variation in social behaviors in an outbred rodent population. Previously, it has been demonstrated that there are strain differences in conditioned place preference/aversion, social interaction, and social novelty-seeking in rodents (Knoll et al, 2018, Moy et al, 2009, Pinheiro et al, 2016, Ryan et al, 2008; however, all these studies were performed in inbred populations.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the limitations of the single gene approach, Molenhuis et al proposed that animal models should evaluate the clinical impact of etiological factors on continuous behavioral traits across varying genetics backgrounds. This is done through a classical approach using genetic mapping of quantitative traits in inbred lines of mice . This approach has been used in the context of autistic‐like phenotypes to identify quantitative trait loci (QTLs) underlying social interaction differences between C57BL/6J and the BTBR mouse model …”
Section: Introductionmentioning
confidence: 99%